The role of motivation in the formation of professional competence in foreign students in the pre-university period - Evgeniya, Kositsyna (2021)
The article analyzes the role of motivation in the professional development of a person. The article proves that the formation of professional competence should begin in the period of training foreign students. The author studies the concept of professional competence and its components. The article explains the role and significance of motivational processes in the formation of professional competence. The key role in the formation of professional competence in the conditions of preparatory departments is played by Russian as a foreign language. Russian as a foreign language becomes a motivational regulator of educational activity. Knowledge of the Russian language helps a foreign student to consider educational goals as personally significant